Producer Services, Manufacturing Linkages, and Trade - Joseph Francois; Julia Woerz (FIW - Research Centre International Economics, 2007)
Working with a mix of panel data on goods and services trade for the OECD for 1994-2004, combined with social accounts data (i.e. data on intermediate linkages) for 78 countries benchmarked to 2001, we examine the role of services as inputs in manufacturing, with a particular focus on indirect exports of services through merchandise exports, and also on the related interaction between service sector openness and the overall pattern of manufacturing exports. From the crosssection, we also develop a set of stylized facts linking services to level of development and the density of intermediate linkages. We find significant and strong positive effects from increased business service openness (i.e. greater levels of imports) on industries like machinery, motor vehicles, chemicals and electric equipment, supporting the notion that off-shoring of business services may promote the competitiveness of the most skill and technology intensive industries in the OECD. Conversely, we find evidence of negative general equilibrium effects for sectors that are less service intensive.
Keywords: 330; Producer Services; Service Sector Openess; Manufacturing linkages; Trade in Services; Indirect export of Services; Manufacturing Sector